LINKING VEGETATION AND MASS MOVEMENTS ON THE HIGH BLUFF AT PAKS-DUNAKÖMLŐD - Magyar, Á.; Kovács, M.; Varga, G.; Radvánszky, B.; Fábián, Sz.; Izsák, T.; Płaczkowska, E.; Tymchenko, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Man subserves to emergence of mass movements with radical changing of the natural land cover. The evolution of landslides affects plant cover and the latter reacts to further terrain development. In Hungary, recurring landslides have emerged along the Danube, the Paks-Dunakömlőd embankment representing a classic type of mass movement effects. Anthropogenic pressures and surface movements in the study area have changed the natural associations resulting in an increase in the number of invasive (Robinia pseudoacacia, Ailanthus altissima) and cosmopolitan (Sambucus nigra, S. ebulus) species. The plant survey was based on classification of zones according to habitat. The tree species were counted in 25 m2 rectangular plots, whereas for the other plants – if they were present – the distribution was estimated for different classes of the high bank. Natural woodland associations only survived on the gentler sloping areas. Mainly nitrogen-loving species have settled down at the foot of the bluff and in its gullies. The mosaic discontinuity of the grass cover becomes dominant on the upper and steeper part of the loess bank. Less undergrowth with homogenous filiform grass characterizes the areas affected by surface movements. Parallelism can be discovered here between the appearance of plant species and their number. Perennial grasses tend to appear on larger or smaller ledges or on hard-to-reach edges. The vegetation cover is rare and patchy, with loess bedrock appearing at the surface at many places. There is hardly any soil where plants root in the loess, and calcium-loving plants settle down here as well. Scarce woody plants partially obstruct the failure of bluffs. However, in the active landsliding areas, the number and the size of trees are limited. To conclude, the vegetation pattern of the study area is well suited for different height and shape classes of the bluffs.
Keywords: mass movements; high bluff; landslide; plant species; Danube; Paks